YOUNG PEOPLE’S EXPERIENCES IN YOUTH-LED PARTICIPATORY ACTION RESEARCH FOR HIV/AIDS PREVENTION - Keiko Goto; Jennifer Tiffany; Gretel Pelto; David Pelletier (International Journal of Child, Youth & Family Studies, 2012)
As part of a project in the UNICEF-initiated “What every adolescent has a right to know” (RTK) program, qualitative interviews were conducted with youth (13 to 21 years of age) who were reached through a youth-led participatory action research (PAR) project. The interviews were conducted with both urban and rural participants in a Caribbean country where potential exposure to HIV/AIDS represents a significant threat to young people’s health. The purpose of the study was to examine how a truly youth organized PAR effort was perceived by the adolescents who were reached through the project. The results suggest that the central role played by youth researchers (the PAR community leaders) created a mode of participation that facilitated the collaboration of at-risk and marginalized youth. The type of engagement created was distinct from modes of participation fostered when adults alone worked with youth.